2015
DOI: 10.1016/j.immuni.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

MCPIP1 Endoribonuclease Activity Negatively Regulates Interleukin-17-Mediated Signaling and Inflammation

Abstract: SUMMARY Interleukin-17 (IL-17) induces pathology in autoimmunity and infections; therefore constraint of this pathway is an essential component of its regulation. We demonstrate that the signaling intermediate MCPIP1 (also termed Regnase-1, encoded by Zc3h12a) is a feedback inhibitor of IL-17 receptor signal transduction. MCPIP1 knockdown enhanced IL-17-mediated signaling, requiring MCPIP1’s endoribonuclease but not deubiquitinase domain. MCPIP1 haploinsufficient mice showed enhanced resistance to disseminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
158
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(167 citation statements)
references
References 61 publications
(119 reference statements)
9
158
0
Order By: Relevance
“…51 More recently, a study showed that another DUB [MCPIP1 (also named Regnase-1)] served as a negative regulator of IL-17 signaling. 53 Unexpectedly, its endoribonuclease but not its deubiquitinase activity was required for the suppression of IL-17 signaling. Mechanically, MCPIP1 inhibits IL-17-mediated signaling and inflammation by degrading the Il6, Nfkbiz, Il17ra and Il17rc mRNAs.…”
Section: Il-17 Family Cytokine-mediated Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…51 More recently, a study showed that another DUB [MCPIP1 (also named Regnase-1)] served as a negative regulator of IL-17 signaling. 53 Unexpectedly, its endoribonuclease but not its deubiquitinase activity was required for the suppression of IL-17 signaling. Mechanically, MCPIP1 inhibits IL-17-mediated signaling and inflammation by degrading the Il6, Nfkbiz, Il17ra and Il17rc mRNAs.…”
Section: Il-17 Family Cytokine-mediated Signaling Pathwaysmentioning
confidence: 99%
“…Mechanically, MCPIP1 inhibits IL-17-mediated signaling and inflammation by degrading the Il6, Nfkbiz, Il17ra and Il17rc mRNAs. 53 IL-17B and IL-17E IL-17RB (also designated IL-17BR or IL-17Rh1) is the receptor for IL-17E. 28 Despite its lower binding affinity compared with IL-17E, IL-17B has also been reported to be a ligand for IL-17RB.…”
Section: Il-17 Family Cytokine-mediated Signaling Pathwaysmentioning
confidence: 99%
“…NF-kB regulates the gene promoter activity of ABIN-1, inducing its mRNA as a late expression gene compared with the A20 expression after TNF-a stimulation (13,24). These data thus suggested that ABIN-1 is part of a similar negative feedback loop, analogous to other IL-17 signaling inhibitors such as A20 and MCP1-induced protein 1/Regnase-1 (7,36). Indeed, in HeLa cells NF-kB was found to induce expression of ABIN-1, whereas ABIN-1 in turn repressed NF-kB activity (13).…”
Section: Discussionmentioning
confidence: 80%
“…In addition to this down regulation of inflammation via the deubiquinase activity of MCPIP, the RNase activity of MCPIP destabilizes and causes degradation of the transcripts of inflammatory cytokines such as IL-1β and IL-6 by binding to the stem loop structure at 3'-UTR of the mRNA 21 . MCPIP can also degrade 3'-UTR-independent degradation of mRNA of the receptors of inflammatory cytokines such as IL-17 22 . Even though RNase activity-dependent degradation of IL-17 receptor transcript was shown to be independent of its UTR, the structural features of the transcript involved in the binding and degradation of IL-17 receptors remain unknown.…”
Section: Molecular Mechanisms Of Mcpip-mediated Preconditioningmentioning
confidence: 99%
“…Deubiquiniase activity inhibits NF-κB activation and probably regulates the ubiquitination state of proteins that can determine their subcellular localization, function and fate. The RNase activity destabilizes and enhances degradation of mRNA for inflammatory cytokine and their receptors 21,22 . The anti-Dicer RNase activity inhibits synthesis of microRNAs (miRs) that can influence cellular function in many ways 25 .…”
Section: Molecular Mechanisms Of Mcpip-mediated Preconditioningmentioning
confidence: 99%